Unemployment insurance in America: a model for Europe? - Lenaerts, Karolien; Paquier, Olivier; Simonetta, Suzanne (Brussels, 2017)
"After the crisis, the longstanding debate on a European unemployment benefits scheme (EUBS) was revived as part of a much larger debate on the need for a supranational automatic stabilisation function for Europe. The American unemployment insurance (UI) system, given its two-tier structure, has often been regarded as a model for a potential EUBS. Previous research has examined the lessons to be learned from the US UI. This paper builds on this literature but goes one step further as it carefully assesses whether the lessons from the US system could actually be implemented in a European context. Indeed, while there are important parallels between the US and the EU in some areas, significant differences in others may complicate implementation or even render it impossible. In this paper, the aim, therefore, is to identify the aspects of the US system to draw inspiration from – in light of the EU’s institutional and political realities – and explain how they inform a potential EUBS. This exercise concentrates on the design and implementation of a potential EUBS. The paper highlights that a two-tier system helps to better attain the goals of unemployment insurance, as demonstrated by the American experience. It also shows the advantages of being pragmatic and taking an incentives-based approach. Other issues, such as solidarity and redistribution, seem more difficulty to tackle in Europe than in the American context and would require further examination. Finally, discretionary measures should be considered with caution."